There is more to pain than tissue damage: eight principles to guide care of acute non-traumatic pain in sport - Caneiro, J. P.; Fukusawa, L.; Hespanhol, L.; Brukner, P.; O´Sullivan, P. P. B. (British Journal of Sports Medicine, 2021)
Musculoskeletal pain in athletes is common, but not always associated with injury (ie, tissue damage). Damage occurs when load exceeds tissue tolerance, such as ligament tear or a fracture. However, pain in athletes that occurs in the absence of trauma and tissue damage is still often labelled an `injury` by clinicians, coaches and athletes themselves. This highlights a gap between knowledge (tissue damage is not necessary for pain) and practice (assuming that all pain arises from tissue damage) in our clinical community. This applies particularly in the area of acute non-traumatic pain (such as back and joint pain). To help bridge this gap, we outline eight principles to guide clinicians who manage musculoskeletal pain in sport.